A figura do professor com contrato temporÃrio: um estudo de caso no ColÃgio Liceu do Conjunto CearÃ - Maria Jose Marques (2006)
ABSTRCAT The aim of this dissertation is to analyze the relations of work (precarization, flexibilization) of temporary teacher, as well as his/her professional routine and the role of Basic Educational Secretary of CearÃ â SEDUC in relationship to the temporary contract, taking into consideration the present day situation of teachers who work in Liceu of Conjunto CearÃ, in Fortaleza. The qualitative research aims to take up the process of the above mentioned teacher in his/her routine, focusing on the way of they are treated. The method of case study is founded in the intensive analysis of a educational institution of second-degree school, sustained with the theoretical contributions of education and social sciences fields, contextualized with political sciences theories of Education Sociology and Work Sociology. The changes occurred in the work environment and the phenomenon so called globalization engendered new kinds of work modalities. The methodological procedures of investigation comprised the period of 2002/2004 and undertook a field, documental and bibliographical research, subsidized by a questionnaire and by the technique of a semi-structured interview applied to a set of social actors, as wit: 23 teachers, the administrating group of school, representatives of Teachers Association of CearÃ â APEOC and the Unique Union of Education Workers â SINDIUTE and four technicians of Regional Centre of Education Development (CREDE) and SEDUC. The results showed the idea the temporary contract teachers of the school under investigation exert your working functions in the informal system, with no underwritten work document and have no working rights assured, experiencing a tough process of professional devaluation surrounded by the watchwords defended by the CearÃÂs educational system, as âQualitative Education for everybody and the best school and a better lifeâ. These teachers have no possibility of extern their opinions as regards the working decisions. They usually receive their salaries with delay without other working rights due the ones approved in public examinations. They are considered dispensable since every semester they are obliged to change their workplace, with the interruption of their docent work. There is need of a fairer work policy which promotes every worker, included the teachers class, a quite important element in order to guarantee an education with quality